2012
DOI: 10.1177/1557085111429783
|View full text |Cite
|
Sign up to set email alerts
|

Does It Cost More to Be a Female Offender? A Life-Course Study of Childhood Circumstances, Crime, Drug Abuse, and Living Conditions

Abstract: In this article we use a new and rich longitudinal data set, The Stockholm Birth Cohort Study, which allows us to follow a cohort of girls and boys until they reach 48 years of age. We study differences in the social background and adult living conditions among men and women with different experiences of involvement in crime. It is clear that the female cohort members who have been registered for crime have experienced more disadvantaged childhoods than the males registered for offending. The results also indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 52 publications
2
40
0
3
Order By: Relevance
“…Although this study did not include a comparative gender analysis, existing research suggests that involvement in crime seems to cost women more than their male counterparts [36]. Since we know that rates of female imprisonment are growing, we can predict that the family-level and community-level fallout connected to this trend makes reintegration that much more important.…”
Section: Resultsmentioning
confidence: 95%
“…Although this study did not include a comparative gender analysis, existing research suggests that involvement in crime seems to cost women more than their male counterparts [36]. Since we know that rates of female imprisonment are growing, we can predict that the family-level and community-level fallout connected to this trend makes reintegration that much more important.…”
Section: Resultsmentioning
confidence: 95%
“…This lack of resources manifests itself in different ways, for example in family structure, finances, social problems and poor health (e.g. Farrington et al 2009;Aaltonen et al 2011;Estrada and Nilsson 2012). Some of the declines noted might nonetheless be regarded as somewhat surprising, not least the decline in registered crime among youths who have grown up in families characterised by long-term welfare recipiency.…”
Section: Young Offenders' Childhood Conditions and School Achievementmentioning
confidence: 99%
“…Studies have shown that female offenders who end up being dealt with by the justice system have often grown up in very difficult home conditions (e.g., Mullings, Pollock, and Crouch, 2002;Estrada and Nilsson 2012;Simpson et al, 2008; for reviews of gendered pathways, see also Belknap and Holsinger, 2006).…”
Section: The Life-course Of Female Offendersmentioning
confidence: 99%
“…Giordano et al 2002;Odgers et al 2008;Estrada and Nilsson 2012). In the current study, when we take experiences of drug abuse into account among those with a history of involvement in crime, we only find small differences between the sexes in levels of labour market attachment, social exclusion and mortality.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation